The circadian clock shapes diurnal gene expression patterns linked to glucose metabolic processes in Chinese cabbage - Shan Wang; Kailin Shi; Yufan Xiao; Wei Ma; Yiguo Hong; Daling Feng; Jianjun Zhao (Journal of Integrative Agriculture)
The plant circadian clock temporally drives gene expression throughout the day and coordinates various physiological processes with diurnal environmental changes. It is essential for conferring plant fitness and competitive advantages to survive and thrive under natural conditions through the circadian control of gene transcription. Chinese cabbage (Brassica rapa ssp. pekinensis) is an economically important vegetable crop worldwide, although there is little information concerning its circadian clock system. Here we found that gene expression patterns are affected by circadian oscillators at both the transcriptional and post-transcriptional levels in Chinese cabbage. Time-course RNA-seq analyses were conducted on two short-period lines (SPcc-1 and SPcc-2) and two long-period lines (LPcc-1 and LPcc-2) under constant light. The results showed that 32.7–50.5% of the genes were regulated by the circadian oscillator and the expression peaks of cycling genes appeared earlier in short-period lines than long-period lines. In addition, approximately 250 splicing events exhibited circadian regulation, with intron retention (IR) accounting for a large proportion. Rhythmically spliced genes included the clock genes LATE ELONGATED HYPOCOTYL (BrLHY), REVEILLE 2 (BrRVE2) and EARLY FLOWERING 3 (BrELF3). We also found that the circadian oscillator could notably influence the diurnal expression patterns of genes that are associated with glucose metabolism via photosynthesis, the Calvin cycle and the tricarboxylic acid (TCA) cycle at both the transcriptional and post-transcriptional levels. The collective results of this study demonstrate that circadian-regulated physiological processes contribute to Chinese cabbage growth and development.